Thermal Effect on Structural Interaction between Energy Pile and Its Host Soil - Qingwen Li; Lu Chen; Lan Qiao (Advances in Materials Science and Engineering)
Energy pile is one of the promising areas in the burgeoning green power technology; it is gradually gaining attention and will have wide applications in the future. Because of its specific structure, the energy pile has the functions of both a structural element and a heat exchanger. However, most researchers have been paying attention to only the heat transfer process and its efficiency. Very few studies have been done on the structural interaction between the energy pile and its host soil. As the behavior of the host soil is complicated and uncertain, thermal stresses appear with inhomogeneous distribution along the pile, and the peak value and distribution of stress will be affected by the thermal and physical properties and thermal conductivities of the structure and the host soil. In view of the above, it is important to determine thermal-mechanical coupled behavior under these conditions. In this study, a comprehensive method using theoretical derivations and numerical simulation was adopted to analyze the structural interaction between the energy pile and its host soil. The results of this study could provide technical guidance for the construction of energy piles.